2022
DOI: 10.3390/ijerph192013547
|View full text |Cite
|
Sign up to set email alerts
|

An Explanatory Model of Sport Motivation, Physical Self-Concept and Anxiety as a Function of the Degree of Adherence to the Mediterranean Diet in Future Physical Education Teachers

Abstract: The present research has the objectives of establishing the relationship between motivational climate towards sport, anxiety, and physical self-concept, and identifying the existing relationships between anxiety, motivational climate, and physical self-concept, broken down into (a) developing an explanatory model of the motivational climate towards sport and its relationship with anxiety and physical self-concept, and (b) contrasting the structural model by means of a multi-group analysis according to the degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Regular physical activity engagement also helps to improve body image, which leads to greater body satisfaction and, subsequently, better psychological wellbeing [ 41 ]. Physical sports engagement has been shown to induce the secretion of neurotransmitters which act directly on emotional wellbeing [ 11 ]. Research carried out by Christensen and Galbo [ 42 ] highlighted that the type of physical activity engaged in influences wellbeing perceptions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regular physical activity engagement also helps to improve body image, which leads to greater body satisfaction and, subsequently, better psychological wellbeing [ 41 ]. Physical sports engagement has been shown to induce the secretion of neurotransmitters which act directly on emotional wellbeing [ 11 ]. Research carried out by Christensen and Galbo [ 42 ] highlighted that the type of physical activity engaged in influences wellbeing perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…Another issue that is very much present during adolescence and early adulthood is the preference for high-calorie foods [ 11 ]. The dietary pattern known as the Mediterranean diet was conceived from within the Mediterranean setting.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the physical dimension of self-concept, it was found that participants with a low level of physical activity showed a better effect of the Mediterranean diet in this area. Given such findings, Melguizo-Ibáñez et al ( 44 ) found that in adolescents and young adults, there is a greater concern for the care of body appearance. Likewise, the study carried out by Fernández-Bustos et al ( 45 ) found a higher level of self-concept for young people who show a moderate or vigorous level of physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that the large supply of ready meals, convenience, or lack of time together with inexperience in shopping are the main reasons why the dietary pattern followed varies [12]. The Mediterranean diet is one of the healthiest dietary patterns currently available [13]. It is mainly based on the moderate consumption of foods originating from the Mediterranean area [13].…”
Section: Introductionmentioning
confidence: 99%
“…The Mediterranean diet is one of the healthiest dietary patterns currently available [13]. It is mainly based on the moderate consumption of foods originating from the Mediterranean area [13]. It includes a moderate intake of unsaturated fats, fish, lean meats, fruits, vegetables, nuts, legumes, and a low intake of red meat and saturated fats [13].…”
Section: Introductionmentioning
confidence: 99%